Radiofrequency ablation using the second-generation temperature-controlled diamond tip system in paroxysmal and persistent atrial fibrillation: results from FASTR-AF - Neuzil, Petr; Poty, Herve; de Chillou, Christian; Petru, Jan; Getman, Michael K; Liu, Shufeng; Funasako, Moritoshi; Durand-Dubief, Alexis; Combes, Stéphane; Albenque, Jean-Paul (Journal of interventional cardiac electrophysiology, 2023)
BACKGROUND: Catheter ablation (CA) technology development reflects the need to improve the effectiveness of atrial fibrillation (AF) treatment. Recently, the DiamondTemp Ablation (DTA) RF generator software was updated with a more responsive power ramp. METHODS: DIAMOND FASTR-AF was a prospective, single-arm, multicenter trial. This study sought to characterize the performance of the updated DTA system for the treatment of patients with drug-refractory paroxysmal and persistent AF (PAF and PsAF). The primary effectiveness endpoint was freedom from atrial arrhythmia recurrence following a 90-day blanking period through 12 months, and the primary safety endpoint was a composite of serious adverse events. RESULTS: In total, 60 subjects (34 PAF and 26 PsAF) underwent CA at three centers. Patients were 71.7% male, (age 63.9 ± 10.2 years, with an AF diagnosis duration 3.1 ± 3.9 years and left atrial size 4.4 ± 0.8 cm). Pulmonary vein isolation-only ablation strategy was performed in 34 (56.7%) subjects. The procedural characteristics show a procedure time 90.8 ± 31.6 min, total RF time 14.7 ± 7.7 min, ablation duration 10.7 ± 3.6 s, and fluid infusion 284.7 ± 111.5 ml. The serious adverse event rate was 8.3% (5/60), 3 pulmonary edema and 2 extended hospitalizations. Freedom from atrial arrhythmia recurrence was achieved in 67.6% of subjects by 12 months. CONCLUSIONS: The updated DTA system demonstrated long-term safety and effectiveness through 12 months of post-ablation follow-up for patients with atrial fibrillation. Additionally, procedures were demonstrated to be highly efficient with short procedure times and low levels of fluid infusion. TRIAL REGISTRATION: Sponsored by Medtronic, Inc.; FASTR-AF ClinicalTrials.gov; NCT03626649.
Keywords: recidiva; Humans; lidé středního věku; Temperature; Radiofrequency; venae pulmonales; teplota; Aged; Female; výsledek terapie; senioři; lidé; Atrial Fibrillation; DiamondTemp; katetrizační ablace; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Pulmonary Veins; Recurrence; mužské pohlaví; prospektivní studie; Catheter Ablation; Atrial fibrillation; fibrilace síní; Catheter ablation; Prospective Studies